5th European working conditions survey Overview report - Parent-Thirion, Agnes; Vermeylen, Greet; Houten, Gijs van.; European Foundation for the improvement of living and working conditions (Λουξεμβούργο : Υπηρεσία Επισήμων Εκδόσεων των Ευρωπαϊκών Κοινοτήτων, 2012)
Work plays a significant role in the lives of people, companies and society at large. Since its inception, the European Union has paid considerable attention to work, and improving working conditions is one of its key policy goals. As stipulated in Article 136 of the EC Treaty, Member States should actively work towards 'the promotion of employment' and 'improved living and working conditions', so as to 'make possible their harmonisation while the improvement is being maintained'.
Περιέχει βιβλιογραφία και ευρετήριο.
Ηλεκτρονικό βιβλίο
Keywords: Quality of work life -- European Union countries -- Statistics; Work environment -- European Union countries -- Statistics; Labor supply -- European Union countries -- Statistics; Electronic books